Ventilasi Paru Pasien dengan Penyakit Paru Obstruksi Kronis (PPOK) paska penerapan Pursed Lips Breathing dengan Pendekatan Cognitive Behaviour Ther - Dwi Maryuni; Tintin Sukartini; Ninuk Dian Kurniawati (Critical Medical and Surgical Nursing Journal (CMSNJ), 2019)
Inroduction : Chronic Obstructive Pulmonary Disease (COPD) is a lung disease that has a severe impact on the physical condition and quality of life of the patients. PLB breathing exercises with CBT is one of the non pharmakologis therapies to help COPD’s patients to obtain optimal physical condition and prevent more severe complications. The aimed of this study was to determine the effect of breathing exercises PLB with CBT to changes RR, HR, SaO2, and Retraction Chest Muscles on COPD’s patients at Ruang Palem I RSUD Dr. Soetomo Surabaya.Method : This study was a pre- experimental study. The independent variabel was PLB with CBT. The dependent variabels were RR, HR, SaO2 and retraction chest muscles on COPD’s patients. Sample was 12 respondents. The sample was divided into 2 groups, 6 respondents as treatments group and 6 respondents as a control group. Data were then analyzed using independent t test, paired t test and chi square with level of siginficance p≤0.05.Result : Results showed that RR (p=0.004), HR (p=0.021), and SaO2 (p=0.003).Discussion : It can be concluded that there were influence the PLB breathing exercises with CBT to changing RR, HR and SaO2 on COPD’s patients. Whereas Chest muscle retraction was no effect with breathing exercises PLB with CBT on COPD’s patients at Ruang Palem I RSUD Dr. Soetomo Surabaya. Suggestions for nurses to be able to improve services for special education breathing exercises PLB with CBT in treating COPD’s patients. For further research expected to examine other factors that may help resolve problems in patients with COPD.